Luminescence dosimetry for evaluation of the external exposure in Metlino, upper Techa River valley, due to the shore of the Metlinsky Pond: A feasibility study. (April 2020) - Woda, C.; Hiller, M.; Ulanowski, A.; Bugrov, N.G.; Degteva, M.O.; Ivanov, O.; Romanov, S.; Tschiersch, J.; Shinonaga, T.
Abstract: Luminescence dosimetry was performed using bricks from the former settlement of Metlino, Southern Urals, Russia, to investigate the feasibility of validating the Techa River Dosimetry System (TRDS) 2016 for the shore of the Metlinsky Pond, upper Techa River region. TRDS is a code for estimating external and internal doses for members of the Extended Techa River Cohort. Several brick samples were taken from the north-western wall of the granary, facing the Metlinsky Pond. Samples were measured at different heights and at different depths into the bricks. Dating of the granary was performed by analyzing well shielded bricks. Assessment of the gamma dose-rate at the sample positions was done by thermoluminescent dosimeters and the dose-rate in front of the granary mapped with a dose-rate meter. Anthropogenic doses in bricks vary from 0.8 to 1.7 Gy and show an increase with sampling height. A similar height profile is observed for the current gamma dose-rate, which is compatible with the results of the dose-rate mapping. Implications for validating the TRDS are discussed. Highlights: Excellent luminescence properties were found for quartz extracted from exposed bricks. Dose rate height profile is in agreement with the radioactive contamination pattern. Brick doses from large heights are very homogeneous. Dose height profile is difficult to interpret due to complex changes of exposure geometry.